SYSTEMS AND METHODS FOR DETECTING COGNITIVE DECLINE WITH MOBILE DEVICES - CHEN, Richard, Jia Chuan; SHEN, Jie; JANKOVIC, Filip, Aleksandar; SUNGA, Marc, Orlando; MALJKOVIC, Vera; SIGNORINI, Alessio; JUNG, Hyun, Joon; KOURTIS, Lampros; SONG, Han, Hee; PUGH, Melissa, Anna Maria; MARINSEK, Nicole, Lee; FOSCHINI, Luca; et al. (2023)
Embodiments of the present disclosure relate systems and methods for detecting cognitive decline of a subject using passively obtained data from at least one mobile device. In an exemplary embodiment, a computer-implemented method comprises receiving passively obtained data from at least one mobile device. The method further comprises generating digital biomarker data from the passively obtained data. The method further comprises analyzing the digital biomarker data to determine whether the subject is exhibiting signs of cognitive decline.